(untitled) (ইসলামী আইন ও বিচার | Islami Ain O Bichar, 2023)
From the very beginning of human history tourism has been started. Once people traveled and migrated for the necessity of life but at present, it is a significant industry. Though modern tourism has been spreading up for relieving daily life’s tiredness and affliction, its commercial appeal cannot be deniable. In this study is shown that one-tenth of the transaction of modern world economy goes through tourism sector. The motivation and ingredients of Islamic tourism are different from conventional tourism that’s why spending time and money only for recreational activities are not promoted here. In this study also has described, by studying the verses of Quran and Hadith about tourism, in broader sense tourism is advocated in Islam for thinking, seeking mental satisfaction, discovering, obtaining knowledge about the mystery of the creation of Allah. The preconditions of Islami tourism are halal goods and services, facilities of prayer, halal accommodation, and transportation systems. Islami tourism is becoming popular day by day but because of various obstacles, most of the Muslim countries could not able to improve their tourism sector. Here some advice is provided to improve Muslim tourism sector. সারসংক্ষেপ: পৃথিবীতে পর্যটনের ইতিহাস অতি প্রাচীন। একসময় মানুষ জীবনের প্রয়োজনে পর্যটন করলেও বর্তমান বিশ্বে তা অত্যন্ত গুরুত্বপূর্ণ এক শিল্প। মানুষের নৈমিত্তিক কার্যাবলির একঘেয়েমিতা দূর করে নতুন কর্মোদ্দীপনা সৃষ্টির জন্য আধুনিক পর্যটন শিল্পের উদ্ভব হলেও এর বাণিজ্যিক দিক অস্বীকার করা যায় না। আধুনিক বিশ্ব-অর্থনীতির একদশমাংশ লেনদেন পর্যটন খাতে হয়ে থাকে। ইসলাম অনুমোদিত পর্যটন উদ্দেশ্য ও উপাদানগত দিক দিয়ে প্রচলিত পর্যটন হতে আলাদা। সুতরাং শুধুমাত্র সাময়িক চিত্ত-বিনোদনের উদ্দেশ্যে সময় ও অর্থব্যয় ইসলামের দৃষ্টিতে অনুমোদিত নয়। আল-কুরআনে বর্ণিত পর্যটন সম্পর্কিত আয়াত এবং রাসূল স. এর হাদীসসমূহ অধ্যয়ন করে এই প্রবন্ধে বর্ণনা করা হয়েছে যে, বৃহত্তর অর্থে আল্লাহর সৃষ্টিরহস্য নিয়ে চিন্তা-গবেষণা, আবিষ‹ার, শিক্ষাগ্রহণ, মানসিক প্রশান্তি লাভের জন্যই পর্যটনের নির্দেশনা প্রদান করা হয়েছে। ইসলাম নির্দেশিত পর্যটনের পূর্বশর্ত হলো, হালাল সেবা ও পণ্য, ইবাদাতের সুব্যবস্থা, শরীয়াসম্মত আবাসন ও পর্যটন স্পট, যানবাহন ইত্যাদি। বর্তমান বিশ্বে পর্যটন বেশ জনপ্রিয়তা লাভ করেছে। তবে পৃথিবীর অধিকাংশ মুসলিম দেশ বিভিন্ন কারণে পর্যটন শিল্পকে উন্নত করতে সক্ষম হচ্ছে না। বিশ্লেষণমূলক পদ্ধতিতে রচিত এ গবেষণাকর্মে ইসলামের আলোকে পর্যটনের উন্নয়নে কতিপয় সুপারিশ প্রদান করা হয়েছে।